QUANTIFICATION OF CERAMIDE SPECIES IN BIOLOGICAL SAMPLES BY LIQUID CHROMATOGRAPHY-ELECTROSPRAY TANDEM MASS SPECTROMETRY - Kasumov, Takhar (2010)
We present an optimized and validated liquid chromatography-electrospray ionization tandem mass spectrometric (LC-ESI-MS/MS) method for the simultaneous measurement of concentrations of different ceramide species in biological samples. The method of analysis of tissue samples is based on Bligh and Dyer extraction, reverse-phase HPLC separation and multiple reaction monitoring of ceramides. Preparation of plasma samples also requires isolation of sphingolipids by silica gel column chromatography prior to LC-ESI-MS/MS analysis. The limits of detection and quantification are in a range of 5–50 pg/ml for distinct ceramides. The method was reliable for inter-assay and intra-assay precision, accuracy and linearity. Recovery of ceramide subspecies from human plasma, rat liver and muscle tissue were 78–91%, 70–99%, and 71–95%, respectively. The separation and quantification of several endogenous long-chain and very-long-chain ceramides using two non-physiological odd chain ceramide (C17 and C25) internal standards was achieved within a single 21 min chromatographic run. The technique was applied to quantify distinct ceramide species in different rat tissues (muscle, liver, and heart) and in human plasma. Using this analytical technique we demonstrated that a clinical exercise training intervention reduces the levels of ceramides in plasma of obese adults. This technique could be extended for quantification of other ceramides and sphyngolipids with no significant modification.